Transformasi Digital Bank Syariah di Era Teknologi: Perkembangan, Tantangan dan Peluang Menuju Pertumbuhan Berkelanjutan - Putri Ayu Lestari (Universitas Muhammadiyah Mataram, 2025)
Abstract: This research examines the digital transformation of Islamic banking in the context of technological development. Using a qualitative methodology based on literature review from various scientific sources, this study shows that Islamic banks have undergone significant evolution from conventional systems based on physical interaction to digital services through mobile banking, internet banking, and Islamic fintech. This development is supported by regulations such as Law No. 10/1998 and Law No. 23/1999, which provide the legal foundation for the existence of Islamic banking. OJK data shows improved performance of Islamic banking with a total of 14 Islamic commercial banks and 1,987 branch offices as of December 2024, as well as asset growth from IDR 594,709 billion (2023) to IDR 664,611 billion (2024). The main challenges faced include the need for quality human resource development, strengthening cyber security, consumer protection, and addressing financial literacy gaps. Opportunities that can be leveraged include Indonesia's demographics dominated by internet users and tech-savvy young generations, ease of digital product promotion, and development of innovative products that address community needs. In conclusion, Islamic banks need to leverage the momentum of digitalization while maintaining sharia principles to achieve sustainable growth.Abstrak: Penelitian ini mengkaji transformasi digital perbankan syariah dalam konteks perkembangan teknologi. Menggunakan metodologi kualitatif berbasis penelusuran pustaka dari beragam sumber ilmiah, studi ini menunjukkan bahwa bank syariah telah mengalami evolusi signifikan dari sistem konvensional berbasis interaksi fisik menjadi layanan digital melalui mobile banking, internet banking, dan fintech syariah. Perkembangan ini didukung oleh regulasi seperti UU No. 10/1998 dan UU No. 23/1999 yang memberikan landasan hukum bagi eksistensi perbankan syariah. Data OJK menunjukkan peningkatan kinerja perbankan syariah dengan total 14 bank umum syariah dan 1.987 kantor cabang per Desember 2024, serta pertumbuhan aset dari Rp594,709 miliar (2023) menjadi Rp664,611 miliar (2024). Tantangan utama yang dihadapi meliputi kebutuhan pengembangan SDM berkualitas, penguatan keamanan siber, perlindungan konsumen, dan mengatasi kesenjangan literasi keuangan. Peluang yang dapat dimanfaatkan mencakup demografi Indonesia yang didominasi pengguna internet dan generasi muda yang akrab teknologi, kemudahan promosi produk secara digital, serta pengembangan produk inovatif yang menjawab kebutuhan masyarakat. Kesimpulannya, bank syariah perlu memanfaatkan momentum digitalisasi sambil mempertahankan prinsip-prinsip syariah untuk mencapai pertumbuhan berkelanjutan.